Spiritual formation based on the statue of the catholic movement Warriors of Mary - Milewski, Mariusz (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The aim of this article is to present the principles of spiritual formation for men within the Catholic community known as the Warriors of Mary, as an integral path of personal development and active participation in the life of the Church. The chosen topic stems from the growing need to offer men, who desire to maturely live out their Christian vocation, effective ways to deepen their Catholic spirituality. The analysis focuses on the key elements of formation emphasized in the movement’s statutes: Marian spirituality, Eucharistic life, and active engagement in community life. This study is based primarily on the Statute of the Warriors of Mary and on documents of the Church’s Magisterium that address the formation of the faithful in a similar context. The structure of the article follows the successive elements of the formation process: purpose, method, and means. Particular emphasis is placed on the relational dimension of spiritual growth, including fraternal support and motivation on the path to holiness.